Precarious International Multicultural Education Hegemony, Dissent and Rising Alternatives - Wright, Handel Kashope; Singh, Michael; Race, Richard; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Multiculturalism and multicultural education are at a paradoxical moment. There is work that continues as if the multicultural hegemony was still intact and on the other hand work articulated as if multiculturalism was decidedly passe. The essays in this collection will be of considerable interest to academics, policy makers and students of both multiculturalism and multicultural education principally because they touch on both perspectives but concentrate for the most part on the thorny problematic of the workings of multicultural education in its present precarious moment. Given the renewed, urgent attacks in various western countries, the cottage industry of (3z(Bdeath of multiculturalism(3y (Btexts and the rise of the interculturalism, transnationalism, diaspora alternatives, is multiculturalism dying? Are the ends of multiculturalism- the management or celebration of diversity; representation and recognition for all in society; creation of just and equitable communities at the global, national and local school classroom levels- better theorized and realized through the ascendant alternatives? Representing the precarious moment in Canada, Ireland, Australia, the United States and the United Kingdom, the essays in this collection address these questions and both depict and trouble hegemonic multicultural education and contrast it with its supposed successor regimes.s
Keywords: Education; Education; Education (general).